Gas hydrates of the Antarctic continental margin bottom structures (by geophysical data) - Levashov, S.P.; Yakimchuk, N.A.; Korchagin, I.N.; Bakhmutov, V.G.; Solovyov, V.D.; Bozhezha, D.N. (Reports of the National Academy of Sciences of Ukraine, 2015)
New data on the location of BSR-zones and possible accumulations of gas hydrates in the structures of passive continental margins of the Antarctica are summarized. The efficiency of the new innovative technology of geoelectric and remote geophysical methods used for the study of gas hydrate accumulations and for the building of deep cuts with abnormally polarized layers of the deposit of gas hydrates is shown. An important feature of this technology is that the results obtained can be used as an independent indicator for detecting the gas hydrates in the areas with low amplitude BSR-boundaries of different geneses. It is shown that the region near the South Shetland Islands can be assigned to one of the most promising (with the shelf in the western part of the Ross Sea) areas of gas hydrate accumulations in the Antarctica.